Islam dan Konstruksi Politik Identitas Etnis di Lampung Barat - Yudha, Gesit Yudha (POLITEA, 2023)
This study examines the regional head and legislative elections in West Lampung where elites running as candidates are more likely to choose their partners based on ethnic representation to promote ethnic solidarity in the region. This article aims to explain the Islamic view of understanding the construction of identity politics in West Lampung. In this case, it uses explanatory qualitative which deals with the issue of regional sons becoming the main commodity in ethnic politics. The findings of this article show that Muklis Basri has established friendship and commitment to the traditional and customary leaders of Sai Batin in West Lampung. The form of his attention is that many traditional activities, and traditional Sai Batin ceremonies are made a permanent regional and tourism agenda in West Lampung Regency. Likewise, the proximity to the persuasive approach of the community, Mukhlis can attract community sympathy by paying great attention to local customs and the public interest. The existence of customary balancers has the authority to make decisions about the results of deliberations in this case mobilization to influence voters. From an Islamic perspective, the prevailing construction of blind fanaticism towards a particular group or tribe, known as ashobiyah, is considered contrary to the principles of equality and fraternity emphasized by this religion as well as the importance of viewing individuals based on their qualities, character and deeds, not their origin based on Q.S Al Hujurat:13.